THE OBLIGATION OF PARENTS TO TEACH FARDHU 'AIN KNOWLEDGE TO CHILDREN IN ISLAMIC EDUCATION - Marhamah Marhamah; Rahmat Saputra (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
Religious education constitutes a primary parental responsibility in shaping children's personality and faith. One of the most important manifestations of this responsibility is teaching fardhu ‘ain knowledge, which refers to the essential religious knowledge that every Muslim is individually obligated to learn and practice. This article aims to examine the normative foundations of parents’ obligation to teach fardhu ‘ain knowledge to their children and to identify the scope of fardhu ‘ain knowledge that must be taught based on the Qur’an, Hadith, and the views of Muslim scholars. This study employs a library research method with a normative approach, examining primary sources such as the Qur’an and Hadith, as well as secondary sources including Qur’anic exegeses (tafsīr), Hadith commentaries (sharḥ al-ḥadīth), and scholarly literature on Islamic education and fardhu ‘ain knowledge. The data were analyzed using content and descriptive analyses. The findings indicate that the obligation of parents to teach fardhu ‘ain knowledge is strongly grounded in the Qur’an, Hadith, and the opinions of Islamic scholars. This obligation forms part of the educational trust (amānah) entrusted to parents, aimed at safeguarding children's creed (‘aqīdah), worship (‘ibādah), and moral character (akhlāq) from an early age. The scope of fardhu ‘ain knowledge that must be taught includes Islamic creed, acts of worship (such as purification, prayer, fasting, zakat for those who meet its requirements, and fundamental rulings concerning lawful and unlawful matters), as well as the cultivation of Islamic morals and etiquette appropriate to the child’s stage of development. Therefore, parental instruction in fardhu ‘ain knowledge serves as the primary foundation for nurturing a generation of Muslims who possess sound faith, perform worship correctly, and exhibit noble character.